Infrared drying of bee pollen: effects and impacts on food components - Isik, Ayla; Ozdemir, Murat; Doymaz, Ibrahim (CZECH ACADEMY AGRICULTURAL SCIENCES, 2019)
Infrared radiation drying being one of the innovative drying methods was chosen to perform comparative study at different infrared power levels at 50, 62, 74 and 88 W. Quality attributes such as protein, fat, ash, carbohydrate, vitamin C content, solubility index and colour of infrared dried bee pollen samples were evaluated. The infrared power has a significant effect on the drying and quality characteristics especially colour. Drying time was reduced from 170 to 50 min when the infrared power level increased from 50 W to 88 W. Morphological changes on the surface of bee pollen grains increased with increasing the infrared power. The bee pollen infrared dried at 50 W retained its quality characteristics better than the bee pollens infrared dried at other power levels.
Keywords: colour; drying time; infrared power level; moisture; quality attributes; solubility index; KINETICS; QUALITY; Food Science & Technology